Analisis Yuridis Terhadap Pemidanaan Pengedar Narkotika Dalam Perspektif Teori Pemidanaan Di Pengadilan Negeri Kelas 1a Kota Lubuklinggau (Studi Kasus Putusan 474/Pid.Sus/2025/Pnllg) - M. Alvin Gumay; Agustinus Samosir; Devi Anggreni Sy; Wawan Fransisco (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Legal analysis of the sentencing of narcotics dealers from the perspective of criminal theory at the Class 1A District Court of Lubuklinggau City (Case Study of Decision Number: 474/Pid.Sus/2025/Pnllg). This type of research is normative-empirical. Normative-empirical (applied) legal research is research that examines the implementation or implementation of positive legal provisions (legislation) and written documents in action (factual) on each particular legal event that occurs in society. Data collection techniques include; collecting secondary data (library and written documents) through library studies and document studies and collecting primary data (data on the research object) through interviews with respondents and informants and resource persons. The conclusion in this study is that the Panel of Judges has applied legal provisions appropriately and in accordance with applicable laws and regulations. The sentencing imposed is based on valid evidence according to Article 184 of the Criminal Procedure Code, as well as the fulfillment of the elements of the crime as regulated in Law Number 35 of 2009 concerning Narcotics. The judge in deciding the case has considered the legal and non-legal aspects in a balanced manner, including the Public Prosecutor’s indictment, witness and defendant statements, evidence, and the defendant’s social and psychological conditions. Thus, from a normative and theoretical legal perspective, the sentencing in Decision Number 474/Pid.Sus/2025/PN LLG has fulfilled the principles of justice, legal certainty, and expediency, and is in line with the objectives of sentencing in Indonesian criminal law. Keywords: Criminalization, Dealers, Narcotics Abstrak Analisis Yuridis Terhadap Pemidanaan Pengedar Narkotika Dalam Perspektif Teori Pemidanaan Di Pengadilan Negeri Kelas 1a Kota Lubuklinggau (Studi Kasus Putusan Nomor : 474/Pid.Sus/2025/Pnllg). Jenis penelitian ini normatifi-empiris. Penelitian hukum normative-empiris (terapan), merupakan penelitian yang mengkaji pelaksanaan atau implementasi ketentuan hukum positif (Perundang- undangan) dan dokumen tertulis secara in action (viiienyusu) pada suatu setiap peristiwa hukum tertentu yang terjadi. Teknik pengumpulan data meliputi; pengumpulan data sekunder (kepustakaan dan dokumen tertulis) melalui studi viiienyusu dan studi dokumen dan pengumpulan data primer (data pada obyek penelitian dilakukan) melalui wawancara dengan responden dan informan serta narasumber. Simpulan dalam penelitian ini bahwa Majelis hakim telah menerapkan ketentuan hukum secara tepat dan sesuai dengan peraturan perundang-undangan yang berlaku. Pemidanaan yang dijatuhkan didasarkan pada pembuktian yang sah menurut Pasal 184 KUHAP, serta pemenuhan unsur-unsur tindak pidana sebagaimana diatur dalam Undang Undang Nomor 35 Tahun 2009 tentang Narkotika. Hakim dalam memutus perkara telah mempertimbangkan aspek yuridis dan non yuridis secara seimbang, meliputi dakwaan Jaksa Penuntut Umum, keterangan saksi dan terdakwa, barang bukti, serta kondisi viiienyus dan psikologis terdakwa. Dengan demikian, secara yuridis viiienyusunviii dan teoritis, pemidanaan dalam Putusan Nomor 474/Pid.Sus/2025/PN LLG telah memenuhi prinsip keadilan, kepastian hukum, dan kemanfaatan, serta sejalan dengan tujuan pemidanaan dalam hukum pidana Indonesia. Kata kunci: Pemidanaan, Pengedar , Narkotika